The vinasse and yellow trap as an alternative in the ecological control of radish (Raphanus sativus L.). A practical approach - José Antonio Legua-Cárdenas; Dante Daniel Cruz-Nieto; José Vicente Nunja-García; Félix Gil Caro-Soto (Journal of the Selva Andina Biosphere)
The objective was to determine the dose for whitefly control. The methodology is based on applied research, so the Completely Randomized Block Design was implemented, consisting of 3 blocks and 5 treatments which were: T1 0, T2 10, T3 20, T4 30 and T5 with 40 mL of vinasse/1.6 m2, these were applied from the first week to the fourth week with doses of 10 mL of vinasse/32 mL of water/week/1.6 m2. The physical characteristics of the crop, the number of flies trapped in the trap and the percentage of damage to the radish crop were also evaluated and statistically evaluated using the analysis of variance and Duncan's statistical method. It was determined that the T5 treatment with 40 mL/1.6m2 excelled in the most optimal results, which were the following values: Crops affected:31.67 %, whiteflies per trap:7, crop size: 26.58 cm, plant weight:37.26 g, agricultural yield:7.008 t/ha and bulb diameter:3.15 cm. It is concluded that the application of vinasse is an agro ecological alternative for whitefly control, with the best results being observed with treatment T5.